1980
DOI: 10.1017/s0022172400063415
|View full text |Cite
|
Sign up to set email alerts
|

A note on some Enterobacteriaceae from the faeces of small wild British mammals

Abstract: SUMMARYOver a four-year period 878 samples of faeces were collected from five species of small wild rodents and two species of shrews at sites in England, Scotland and Wales. A search was made for Salmonella in these samples but no isolations of this genus were made. Several other genera of Enterobacteriaceae were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
3
0
0
Order By: Relevance
“…All tested samples were free from Salmonella and this result is congruent with previous studies from the United Kingdom and Canada that regardless of the isolation method reported none or low level (1%) of Salmonella carriage in various rodent species including mice and voles derived from natural, landfill, and farm environments [ 16 , 17 , 18 , 19 ]. Those findings are contradictory to the research on commensal rodents that thrive in the vicinity of human settlements and can serve as vectors in pathogen transmission.…”
Section: Discussionsupporting
confidence: 90%
“…All tested samples were free from Salmonella and this result is congruent with previous studies from the United Kingdom and Canada that regardless of the isolation method reported none or low level (1%) of Salmonella carriage in various rodent species including mice and voles derived from natural, landfill, and farm environments [ 16 , 17 , 18 , 19 ]. Those findings are contradictory to the research on commensal rodents that thrive in the vicinity of human settlements and can serve as vectors in pathogen transmission.…”
Section: Discussionsupporting
confidence: 90%
“…Despite various attempts, no Salmonella isolate was detected in any of the fecal samples tested. These results support the finding of other researchers that Salmonella occurs very infrequently in wild small animals (13,15,28). The low rate of occurrence of E. coli and the absence of Salmonella in the gastrointestinal tracts of wild small mammals may be attributable to the diet of these animals, which can vary depending on the geographic location, the population density, and seasonal variations in the food supply (21,38).…”
Section: Ery Of Nonfastidious Organisms Such As Enterobacteriaceaesupporting
confidence: 90%
“…Rodents do not seem to represent reservoir hosts for pathogenic strains of E. coli (e.g. Healing et al, 1980 ; Kilonzo et al, 2013 ), which was in agreement with our findings (see also Swiecicka et al, 2003 ; Kozak et al, 2009 ). The presence of the bacterium may be related to gut microbiota variations due to diet seasonality ( Ecke et al, 2018 ; Gebczynska, 1983 ; Hansson, 1979 , 1985 ).…”
Section: Discussionsupporting
confidence: 93%